محددات الطلب على التمويل برأس المال الاستثماري – دراسة عينة من المقاولين في الجزائر العاصمة -: determinants of the demand for financing with private equity - a sample study of entrepreneurs in algiers - - ولد عابد عمر; عابد نصيرة (Journal of North African Economies, 2025)
This study aims to identify the various factors that affect the demand for financing with private equity in Algeria, and to study the most important techniques that will revive the private equity market, through a field study of a sample of active entrepreneurs in Algiers, in order to know the extent of Knowing the contractors and informing them about the characteristics of this type of financing In order to reach the goal of the study, it has been divided into three main axes, the first axis deals with the concept of financing with investment capital and its importance, especially for contractors and creators, while the second axis is concerned with the concept of contracting and contractor, while the third axis represented in a field study of a sample of contractors, where it was distributed A questionnaire for them in order to find out the reasons for the weak demand for financing with investment capital, as well as techniques that can help in stimulating demand for it.